(untitled) (Colombia Medica, 2022)
A year and a half after the pandemic, in which efforts have been fundamentally based on avoiding the collapse of hospitals and the development, in record time, of innovative vaccines, a worrying consequence has appeared: clinical sequelae among survivors of this disease. From the overwhelming number of infected people (over 430 million people until February 2022), it was possible to predict that a significant percentage of them was going to develop sequelae, which would make it difficult for them to reintegrate into their jobs, families, and society. Of course, not all infected persons will present sequelae; however, the odds will be significantly higher for the ones affected by the most severe forms of the disease, such as those who suffered acute respiratory distress syndrome (ARDS), and particularly those with comorbidities, as well as older adults. In recent months, this topic has been so important that a new concept related to the persistence of symptoms for more than three months has appeared: persistent COVID, or “long COVID”. Without a doubt, this new condition allows us to think of persistent COVID as a chronic disease; therefore, rehabilitation takes on an even more preponderant role, not only because of the different systems involved but also because of the duration of the sequelae.